MODERASI BERAGAMA DALAM PERSPEKTIF TAFSIR AL-QURAN KEMENAG (Studi Kasus Tindakan Nasaruddin Umar Mencium Kening Paus Fransiskus) - Rohman, Moch Abdul (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2025)
This article discusses the concept of religious moderation in Islam by referring to the tafsir of the Al-Qur'an from the Ministry of Religious Affairs, and analyzes the action of the Grand Imam of Istiqlal Mosque, Nasaruddin Umar, who kissed the forehead of Pope Francis in the context of interfaith meetings. This research aims to explore the understanding of religious moderation based on the principles found in the Al-Qur'an, which emphasizes the importance of a middle ground, justice, and wisdom in interfaith interactions. Through a descriptive-analytical approach, this article examines how Nasaruddin Umar's action can be understood as a manifestation of moderation values, as well as his significant role as a religious leader in fostering harmonious relationships amidst diversity. The analysis results indicate that this action aligns with the teachings of the Al-Qur'an that encourage dialogue and cooperation among religions, while also emphasizing the necessity of maintaining unity and cohesion in a multicultural society. Thus, religious moderation is expected to be a solution for addressing conflicts and strengthening tolerance among adherents of various faiths.